2018
DOI: 10.3390/polym10101129
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of Hybrid Inorganic–Polymer Nanocomposites

Abstract: Hybrid inorganic–polymer nanocomposites can be employed in diverse applications due to the potential combination of desired properties from both the organic and inorganic components. The use of novel bottom–up in situ synthesis methods for the fabrication of these nanocomposites is advantageous compared to top–down ex situ mixing methods, as it offers increased control over the structure and properties of the material. In this review, the focus will be on the application of the sol–gel process for the synthesi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 136 publications
0
47
0
3
Order By: Relevance
“…The homogeneous and complete distribution of the inorganic phase in the organic matrix in the case of hybrid composites favors the enhancement of the interfacial surface area, thus optimizing the organic–inorganic interactions responsible for the improvement of the final properties of the materials. However, this target is difficult to attain, especially due the inherent immiscibility between inorganic and organic phases, reason for that extensive research has been devoted to the chemical modification of inorganic nanoparticles [ 28 ]. The functionalization of CeO 2 nanoparticles with silane sequences aimed to improve the compatibility between the inorganic units and the cellulose matrix with a direct effect on their better dispersion, reduced aggregation and stabilization in the organic material.…”
Section: Resultsmentioning
confidence: 99%
“…The homogeneous and complete distribution of the inorganic phase in the organic matrix in the case of hybrid composites favors the enhancement of the interfacial surface area, thus optimizing the organic–inorganic interactions responsible for the improvement of the final properties of the materials. However, this target is difficult to attain, especially due the inherent immiscibility between inorganic and organic phases, reason for that extensive research has been devoted to the chemical modification of inorganic nanoparticles [ 28 ]. The functionalization of CeO 2 nanoparticles with silane sequences aimed to improve the compatibility between the inorganic units and the cellulose matrix with a direct effect on their better dispersion, reduced aggregation and stabilization in the organic material.…”
Section: Resultsmentioning
confidence: 99%
“…Several strategies have been developed to prepare well‐defined inorganic/organic hybrid NCs. The most common of these strategies are via starlike polymer as nanoreactors, sol–gel, in situ polymerization, and solution blending method . In this study, poly (9,9 ′ ‐di‐n‐octylfluorenyl‐2.7‐diyl) (PFO) as a donor and poly [2‐methoxy‐5‐(2‐ethyl‐hexyloxy)‐1,4‐phenylenevinylene] (MEH‐PPV) as an acceptor were blended at various ratios with and without a SiO 2 /TiO 2 NC by the solution blending method.…”
Section: Introductionmentioning
confidence: 96%
“…96-101-1108, a = b = c = 3.911 Å), 3 This FCC structure can be indexed to its crystalline data (JCPDS card no. 96-901-1613, a = b = c = 4.065 Å), 4 This FCC structure can be indexed to its crystalline data (JCPDS card no. 96-101-1608, a = b = c = 4.079 Å).…”
Section: Xrd Patternsmentioning
confidence: 99%
“…Over the past years, polymers and their related metallic compounds have been considered as promising and suitable materials to modify the enhancement energy and resolve the environmental crisis for many applications such as water treatment, air-batteries, and opto-electronics, due to uniform structures and their surface properties [1][2][3][4]. Several reports have shown that polymers act as stabilizers and hosts for metallic nanoparticles because the functional groups of the polymer chain contain electron-donor functional groups (hydroxyl, amine, etc.)…”
Section: Introductionmentioning
confidence: 99%